Design for Learning in Virtual Worlds. - Nelson, Brian C. (Interdisciplinary approaches to educational technology., 2012)
Design for Learning in Virtual Worlds, the first book focused specifically on how to design virtual worlds for educational purposes, explores: * The history and evolution of virtual worlds; * The theories behind the use of virtual worlds for learning; * The design of curricula in virtual worlds; * Design guidelines for elements experienced in virtual worlds that support learning; * Design guidelines for learning quests and activities in virtual worlds. The authors also examine the theories and associated design principles used to create embedded assessments in virtual worlds. Finally, a framew.